Pertanggungjawaban Hukum atas Pelanggaran Informed Consent dalam Tindakan Kedokteran di Indonesia dan Jepang - NARUMI HAYAKAWA (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The issue of informed consent in emergency medical treatment creates legal problems related to the protection of patient autonomy and the application of the emergency exception doctrine. The research uses a normative juridical method with a comparative approach between the Indonesian and Japanese legal systems. The study shows that Japan has a more progressive system through the strengthening of shared decision-making, hospital risk management and patient rights protection, while Indonesia still faces weaknesses in medical communication standards and the regulation of emergency medical treatment. This study concludes that Indonesia’s health law reform should focus on strengthening hospital liability, protecting patient rights and ensuring legal certainty in emergency medical treatment.